Kiai's Leadership in Strengthening Santri's Moderation Attitude in Islamic Boarding Schools - Arif Khairur Rozaq; Basri Basri; Indah Indah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2022)
This article aims to analyze: 1) the role of the kiai's leadership in strengthening the moderation attitude of the students at the Al-Khoirot Islamic Boarding School, 2) the steps taken by the Kiai, 3) the evaluation carried out by the kiai's leadership. This research uses a qualitative approach, the type of case study. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis was carried out in three steps, namely: data condensation, data presentation, and conclusion. Checking the data's validity is done using the credibility, dependency test, and certainty test. The results of this study are as follows: first, Kiai Pondok Pesantren Al-Khoirot in carrying out his leadership has four roles, namely: Kiai as a guide, Kiai as an agent of change, Kiai as spokesperson, and Kiai as a coach. To achieve the top leadership role, Kiai uses a situational leadership style in the form of delegation, guidance, and direction to subordinates. Second, in shaping and strengthening the moderation attitude of the santri, the Kiai emphasizes the study of books by the Kiai and the curriculum. Third, the implementation of the Kiai's leadership in strengthening the religious moderation of students at the Al-Khoirot Islamic Boarding School has not encountered significant obstacles. Likewise, the implementation of strengthening the attitude of religious moderation of students by the expectations of the Kiai. The daily characteristics of santri in implementing the attitude of religious moderation are good.